Au@CdS Core–Shell Nanoparticles‐Modified ZnO Nanowires Photoanode for Efficient Photoelectrochemical Water Splitting. Issue 12 (17th July 2015) - Guo, Chun Xian; Xie, Jiale; Yang, Hongbin; Li, Chang Ming
Abstract : Hydrogen production from water splitting using solar energy based on photoelectrochemical (PEC) cells has attracted increasing attention because it leaves less of a carbon footprint and has economic superiority of solar and hydrogen energy. Oxide semiconductors such as ZnO possessing high stability against photocorrosion in hole scavenger systems have been widely used to build photoanodes of PEC cells but under visible light their conversion efficiencies with respect to incident‐photon‐to‐current conversion efficiency (IPCE) measured without external bias are still not satisfied. An innovative way is presented here to significantly improve the conversion efficiency of PEC cells by constructing a core–shell structure‐based photoanode comprising Au@CdS core–shell nanoparticles on ZnO nanowires (Au@CdS‐ZnO). The Au core offers strong electronic interactions with both CdS and ZnO resulting in a unique nanojunction to facilitate charge transfer. The Au@CdS‐ZnO PEC cell under 400 nm light irradiation without any applied bias provides an IPCE of 14.8%. Under AM1.5 light illumination with a bias of 0.4 V, the Au@CdS‐ZnO PEC cell produces H2 at a constant rate of 11.5 μmol h −1 as long as 10 h. This work provides a fundamental insight to improve the conversion efficiency for visible light in water splitting. Abstract : A photoanode of Au@CdS core–shell nanoparticle‐modified ZnO nanowires with a favorable charge transfer nanojunction is built for photoelectrochemical water splitting, providing an incident‐photon‐to‐current conversion efficiency of 14.8% without any applied bias, and H2 production at a constant rate of 11.5 μmol h −1 for 10 h at 0.4 V bias under AM1.5 illumination.